Sea Water Intake Building Based on Revetment and Groins Structures - Putera Agung Maha Agung; Dandung Novianto (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
An open sea water intake structure is designed without desalination treatment system at the port area. Fresh water from intake system later on is used for refrigeration system. Function of intake structure is to collect water with special characteristic issue to minimize the volume of sand sediment entered in the intake pipe. Floating and suspended sediment particles passed by the pipe filter causes negative impact and damage to the pump and or heat exchanger systems in Power Plant, so it must be cleaned periodically and requires extra costs. New design of sea water intake at study area uses revetment and groin system to retain the floating and suspended sand sediment, the structure system is able to be expected retaining all sediment particle types and cost maintenance of intake system can be reduced.